PENERAPAN PEMBELAJARAN DENGAN PENDEKATAN MATEMATIKA REALISTIK BERBANTUAN TOKEN EKONOMI DALAM MENINGKATKAN KEMAMPUAN LITERASI MATEMATIKA - MM. Endang Susetyawati; Kintoko Kintoko; Lisa Oktavia; Nadia Maharani Putri (LPPM Universitas Bina Bangsa, 2024)
Mathematics is a basic science that is very important to underlie the development of other sciences. Students are required to master several abilities in mathematics, one of which is mathematical literacy. This research aims to increase mathematical literacy by applying the PMRI approach assisted by economic tokens. This research uses quantitative research with quasi-experimental methods. The results of this research are that the application of the PMRI approach assisted by economic tokens can improve student learning outcomes, especially in mathematical literacy. This can be seen from the test results before and after using the PMRI application with the help of economic tokens. The percentage of achievement of mathematical literacy skills for each indicator shows that: the first indicator of 84.4% is in the Good category, the second indicator of 66.7% is in the Fair category, and the third indicator of 88.7% is in the Very Good category